Log in to add a comment

Log in to add a comment

The Brainliest Answer!

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

[ (0.4)³ - (0.24)³ ] / [ (0.4)² + 0.4 * 0.24 +(0.24)² ]

We know that a³ - b³ = (a-b)(a² + ab + b²)

=[(0.4 - 0.24)( (0.4)² + 0.4 * 0.24 + (0.24)² )] / [ (0.4)² + 0.4 * 0.24 +(0.24)²]

Since denominator is already in form a² + ab + b², the second bracket in numerator and the denominator get cancelled.

So, we have a - b left

= 0.4 - 0.24

=**0.16**

We know that a³ - b³ = (a-b)(a² + ab + b²)

=[(0.4 - 0.24)( (0.4)² + 0.4 * 0.24 + (0.24)² )] / [ (0.4)² + 0.4 * 0.24 +(0.24)²]

Since denominator is already in form a² + ab + b², the second bracket in numerator and the denominator get cancelled.

So, we have a - b left

= 0.4 - 0.24

=

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Given [ (0.4)^3 - (0.24)^3 ] / [ (0.4)^2 + 0.4 * 0.24 +(0.24)^2 ]

this is in the form of { (a-b)(a^2+ab+b^2) }

= [(0.4 - 0.24)( (0.4)^2 + 0.4 * 0.24 + (0.24)^2 )] / [ (0.4)^2 + 0.4 * 0.24 +(0.24)^2]

= 0.4 - 0.24 ( remaining get canceled )

= 0.16 ....

hence solved

hope it's help u

this is in the form of { (a-b)(a^2+ab+b^2) }

= [(0.4 - 0.24)( (0.4)^2 + 0.4 * 0.24 + (0.24)^2 )] / [ (0.4)^2 + 0.4 * 0.24 +(0.24)^2]

= 0.4 - 0.24 ( remaining get canceled )

= 0.16 ....

hence solved

hope it's help u